Intake and diet preference of dairy heifers grazing mixed or alternating rows of birdsfoot trefoil and cool‐season grasses - Michael D. Peel; Blair L. Waldron; Jacob T. Briscoe; Marcus F. Rose; S. Clay Isom; Kara J. Thornton; Jacob A. Hadfield; Kerry A. Rood; J. Earl Creech (Grassland Research)
Abstract Background Mixtures with birdsfoot trefoil (BFT) increase herbage intake in grazing cattle. We hypothesized that BFT spatially separated from grasses would increase preferential grazing of BFT and herbage intake compared to grass and BFT in mixed rows. Methods Binary mixtures of BFT were established with orchardgrass, meadow bromegrass, tall fescue, and perennial ryegrass in alternating and in mixed rows. Pastures were rotationally stocked with Jersey heifers, and herbage mass, intake, and preferential grazing were estimated. Results Planting BFT in alternating rows did not affect herbage mass, intake, or BFT preference. Regardless of spatial arrangement, pasture production averaged 4116 kg ha−1 per rotation, of which 32% was BFT. BFT comprised 39% of herbage intake in alternating and mixed rows, 7% greater (p = 0.001) than offered, indicating partial preference for BFT. Greatest preferential grazing of BFT was in tall fescue and orchardgrass mixtures, but less than commonly reported for legumes grown in more contrasting spatial arrangements with cool‐season grasses. Conclusions Grazing heifers showed partial preference for BFT over grass. However, the lack of an effect of spatial arrangement on herbage mass, herbage intake, and diet preference indicates that spatial arrangements greater than alternating rows may be needed to increase overall herbage intake.